2018
DOI: 10.1083/jcb.201801168
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy balances mtDNA synthesis and degradation by DNA polymerase POLG during starvation

Abstract: Medeiros et al. show that mtDNA polymerase POLG controls mtDNA copy number in the context of autophagy-mediated metabolic homeostasis. After prolonged starvation, the mtDNA degradative activity of POLG is activated to adjust the increasing mtDNA copy number in WT cells, whereas in autophagy-deficient cells, POLG’s continued degradative activity causes mtDNA instability and respiratory dysfunction as a result of nucleotide insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 48 publications
(66 reference statements)
3
48
0
Order By: Relevance
“…Next, we tried to monitor mtDNA synthesis by in vivo incorporation of the thymidine analogue 5-ethynyl-2′-deoxyuridine (EdU) during the zygote development. EdU incorporation was visualized in fixed cells with Alexa Fluor 488 using copper click chemistry, following a protocol reported for Saccharomyces cerevisiae 35 . a-and α-haploid cells were transferred to hay cube agar plates supplemented with EdU and allowed to form zygotes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we tried to monitor mtDNA synthesis by in vivo incorporation of the thymidine analogue 5-ethynyl-2′-deoxyuridine (EdU) during the zygote development. EdU incorporation was visualized in fixed cells with Alexa Fluor 488 using copper click chemistry, following a protocol reported for Saccharomyces cerevisiae 35 . a-and α-haploid cells were transferred to hay cube agar plates supplemented with EdU and allowed to form zygotes.…”
Section: Resultsmentioning
confidence: 99%
“…edU labelling of zygotes. EdU labeling was performed using a kit (Click-iT Plus Alexa488 imaging kit, Thermo Fisher Scientific, Waltham, MA USA) and following a protocol reported for S. cereviciae 35 . Mating of C. neoformans was induced on hay cube agar plates, on which 200 µL of 1 mM EdU (5′-ethynyl-2′-deoxyuridine) was spread and dried.…”
Section: Methodsmentioning
confidence: 99%
“…8D). Reactive oxygen species (ROS) accumulate in autophagy-deficient cells under nitrogen starvation (42,43) and in mitophagy-deficient cells under starvation after respiratory growth (44). It is possible that ROS released from excess mitochondria accumulate in atg2⌬ or atg32⌬ cells in ethanoldepleted phase; if so, these ROS could damage cellular components in a way that inhibits rapid adaptation to fresh medium.…”
Section: Analysis Of Autophagy In Batch Culture On Low-glucose Mediummentioning
confidence: 99%
“…Recent work done has shown that MIP1, the yeast homolog of POLG, controls mtDNA copy number by regulating mtDNA synthesis and degradation in starving yeast cells which were deficient in Atg7 (DAtg7) [53]. Atg7 is a conserved component of the ubiquitinlike system required for autophagy in yeast [54].…”
Section: Analysis Of the Mtdna Point Mutation Load In The Livers Of Ymentioning
confidence: 99%